2018
DOI: 10.1002/dta.2506
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally monitoring of P‐III‐NP, IGF‐I, and GH‐2000 score increases the probability of detecting two weeks’ administration of low‐dose recombinant growth hormone compared to GH‐2000 decision limit and GH isoform test and micro RNA markers

Abstract: To detect doping with growth hormone (GH), GH isoform and biomarkers tests are available. Both methods use population-based decision limits. Future testing in anti-doping is progressing toward individual-based reference ranges, and it is possible that with such an approach the sensitivity to detect GH doping may increase. In addition to monitoring different proteins, the use of miRNAs as future GH biomarkers has been discussed. Here we have longitudinally studied the serum concentrations of IGF-I, P-III-NP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…This study confirmed the observations of Lehtihet et al 21 on the difficulty of detecting GH microdoses using the methods validated for anti-doping analysis. Only one subject would have been suspected of using GH when tested 24 hours after an injection with the direct isoform test and none with the GH biomarker test.…”
Section: Detection Of Recombinant Gh Microdosessupporting
confidence: 91%
See 3 more Smart Citations
“…This study confirmed the observations of Lehtihet et al 21 on the difficulty of detecting GH microdoses using the methods validated for anti-doping analysis. Only one subject would have been suspected of using GH when tested 24 hours after an injection with the direct isoform test and none with the GH biomarker test.…”
Section: Detection Of Recombinant Gh Microdosessupporting
confidence: 91%
“…IGF‐I was a more sensitive marker than P‐III‐NP with more than half the subjects above the upper limit 24 hours after the fifth dose. This very low effect of GH microdoses on P‐III‐NP probably indicates that only higher doses enable a significant and prolonged increase, as already observed by Lehtihet et al when comparing low doses (1 IU/day) and high doses (4 IU/day). These observations nonetheless support the idea that monitoring intra‐individual variations can be more of a deterrent to GH abuse than the actual methods.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Neither of the participants using recGH tested positive with the GH isoform test. We did not conduct the GH2000 biomarker test since in a previous study where recGH doses in the same range were administered, only the GH isoform test could detect recGH . The use of growth hormone releasing peptides/secretagogs was reported in seven participants and surprisingly one was tested positive on ibutamoren (also known as MK‐677), even though according to the questionnaire it was administered as droplets 8 weeks earlier.…”
Section: Discussionmentioning
confidence: 99%